After neoliberalisation? Monetary indiscipline, crisis and the state. Issue 1 (29th August 2017) - Green, Jeremy; Lavery, Scott
Abstract : Across the advanced capitalist states, the post‐crisis conjuncture has been characterised by both marked continuity and profound change. While regressive distributional trends in place before the 2008 crisis have intensified, a number of highly unorthodox policy interventions have also emerged. In particular, a new regime of "loose" monetary policy has crystallised, exemplified by record low interest rates and sustained programmes of quantitative easing. Existing approaches within economic geography are, we contend, ill‐equipped to deal with these transformations. Engaging with the "variegated neoliberalisation approach" – associated with Jamie Peck and his collaborators – the article argues that existing conceptualisations of neoliberalisation understate the key significance that central state institutions play in securing advanced capitalist development. They therefore miss the key role that monetary indiscipline has played in sustaining capitalist development since 2008. This argument is substantiated empirically through a case study of state intervention in the UK housing market in the post‐crisis conjuncture. Focusing on the Help to Buy Scheme and the buy‐to‐let market, the article argues that the UK's loose monetary policy regime has produced novel patterns of spatial divergence across the UK regions while simultaneously consolidating the UK's dysfunctional financialised model of capitalism.